2017
DOI: 10.1002/anie.201707529
|View full text |Cite
|
Sign up to set email alerts
|

4,5,9,10‐Pyrene Diimides: A Family of Aromatic Diimides Exhibiting High Electron Mobility and Two‐Photon Excited Emission

Abstract: The design and synthesis of high-performance n-type organic semiconductors are important for the development of future organic optoelectronics. Facile synthetic routes to reach the K-region of pyrene and produce 4,5,9,10-pyrene diimide (PyDI) derivatives are reported. The PyDI derivatives exhibited efficient electron transport properties, with the highest electron mobility of up to 3.08 cm V s . The tert-butyl-substituted compounds (t-PyDI) also showed good one- and two-photon excited fluorescence properties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 33 publications
3
58
0
3
Order By: Relevance
“…DBP thin films demonstrate a mobility of 0.21 cm 2 V −1 s −1 and blue emission with a PLQY of 47%; 1,6‐PyE thin films demonstrate a mobility of 0.17 cm 2 V −1 s −1 and 1,6‐PyE single crystals demonstrate yellow‐green emission with a PLQY of 28.8%; and 2,7‐PyE thin films demonstrate a mobility of 1.66 cm 2 V −1 s −1 and 2,7‐PyE single crystals demonstrate blue emission with a PLQY of 27.4%. More recently, Wu et al designed and synthesized a new series of pyrene derivatives, 4,5,9,10‐pyrenediimide (PyDI) derivatives, and found that the compound substituted with an n ‐pentyl moiety, C 5 ‐PyDI, exhibited efficient electron‐transport properties, with the highest electron mobility of 3.8 cm 2 V −1 s −1 , while its tert ‐butyl‐substituted compound, t‐C5‐PyDI, showed good two‐photon excited fluorescence properties . The chemical structures of the high‐mobility emissive anthracene and pyrene derivatives discussed above are shown in Scheme .…”
Section: High‐performance Optoelectronic Materials For Osscsmentioning
confidence: 99%
“…DBP thin films demonstrate a mobility of 0.21 cm 2 V −1 s −1 and blue emission with a PLQY of 47%; 1,6‐PyE thin films demonstrate a mobility of 0.17 cm 2 V −1 s −1 and 1,6‐PyE single crystals demonstrate yellow‐green emission with a PLQY of 28.8%; and 2,7‐PyE thin films demonstrate a mobility of 1.66 cm 2 V −1 s −1 and 2,7‐PyE single crystals demonstrate blue emission with a PLQY of 27.4%. More recently, Wu et al designed and synthesized a new series of pyrene derivatives, 4,5,9,10‐pyrenediimide (PyDI) derivatives, and found that the compound substituted with an n ‐pentyl moiety, C 5 ‐PyDI, exhibited efficient electron‐transport properties, with the highest electron mobility of 3.8 cm 2 V −1 s −1 , while its tert ‐butyl‐substituted compound, t‐C5‐PyDI, showed good two‐photon excited fluorescence properties . The chemical structures of the high‐mobility emissive anthracene and pyrene derivatives discussed above are shown in Scheme .…”
Section: High‐performance Optoelectronic Materials For Osscsmentioning
confidence: 99%
“…Compounds 3 and 5 were synthesized according to the literatures. 25,28 The synthetic routes for b-diketonate boron complex BF 2 -TP were shown in Scheme 2. Firstly, the tetraphenylethene derivative 3 was synthesized by Suzuki-Miyaura coupling between 1 and boric acid 2.…”
Section: Synthesismentioning
confidence: 99%
“…[10] Elemental analyses were performed on aP erkin-Elmer 2400 Series II analyzer.S imilarly to other reported fused-NHBs, [10] we were unable to obtain C,H,N-values for 3, 4, 8,a nd 11 due to air-and moisture-sensitivity.A ll chemicals were purchased from commercial sources and used directly unless noted otherwise. The 1,3-bis(2,6-diisopropylphenyl)imidazolium chloride (IPr•HCl), [34] 4,5,9,10-tetrabromo-2,7-ditert-butylpyrene, [35] and compound 1 [22][23] were prepared according to the literature procedures.…”
Section: General Informationmentioning
confidence: 99%